Charged Microdroplets Deposition for Nanostructured-Based Electrode Surface Modification - Rosaceleste Zumpano; Marco Agostini; Franco Mazzei; Anna Troiani; Chiara Salvitti; Marta Managò; Alessia Di Noi; Andreina Ricci; Federico Pepi (Surfaces)
Accelerated synthesis of gold nanoparticles (AuNPs) in charged microdroplets produced by electrospray ionization (ESI) was exploited to modify the surface of graphite screen-printed electrodes (GSPEs). The deposited AuNPs were then functionalized by the charged microdroplets deposition of 6-ferrocenyl-hexanethiol (6Fc-ht) solutions that act as reducing and stabilizing agents and provide electrochemical properties for the modified electrodes. The morphology and composition of the AuNPs were characterized by scanning electron microscopy (SEM). Cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) were used to investigate the electrochemical behavior of the modified electrodes. The results showed that the ESI microdroplets deposition technique produces uniform and well-dispersed AuNPs on GSPE, and optimal conditions for deposition were identified, enhancing GSPE electrocatalytic performance. Further functionalization by ESI microdroplets of AuNPs with 6Fc-ht demonstrated improved redox properties compared with the conventional self-assembled monolayer (SAM) method, highlighting the technique’s potential for the easy and fast functionalization of electrochemical sensors.